Zbrzyca – dopływ Łaby? O motywach kaszubsko-połabskich i presji kulturowej w poezji Stanisława Pestki (Jana Zbrzycy) - Kalinowski, Daniel (Slavia Occidentalis, 2016)
This article deals with the images of Slavic cultural space in north-western Europe presented in Stanislaw Pestka’s works written in the Kashubian language. His poetic descriptions, reflect the profound relations between Kashubian tradition and north-western Slavic culture. They mainly present the struggle for cultural identity, similar in both cultures. In contemporary Europe, both Kashubs and Polabs are minorities facing the threat of extinction, subjected to numerous factors of acculturation and assimilation. The only chance for the salvation of the Kashubs is to counteract the cultural processes which resulted in the cultural dependence of the Slavic inhabitants of Lusatia, Mecklenburg and Pomerania on militarily and economically stronger neighbours.